Africa in the Era of Globalization: Issues and Prospects - Offiong, Ekwutosi; Ellah, Timothy Ogbang; Effiong, Eke Nta; Inyang, Etim Bassey (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Globalization is a recent terminology that has revolved around the stimulated technologies of the late 1980s and 1990s. The aspects of globalization this study adopts revolve around the aptness in the transportation system, the advent of satellite communication, improvement within the banking and telecommunications sectors, foreign investment and market integration, etc. Others include - diminishing state-centric political economy and military rivalries to dominate the international system after the Cold War since national borders cannot stop the flow of information and other technological development. This study discovered that Africa is still far from attaining every necessary index to be part of the globalized era. What Africa contributes to the era presently is raw materials, and further pays heavily to buy from global technologies. The study made use of secondary sources of data gathering to boost the content of the research. The study is of the view that Africa can only benefit effectively from the era of globalization if she effectively develops a home-grown technology, upgrade her infrastructure to meet up with the 21st-century standard, and train her human resources in the science of innovation and inventions, etc. The study believes that - Africa like Japan, China, and Korea can still catch up with the first world if it can look inward and harness its human and natural resources effectively for effective competition in the era of globalization.